A Behavior-Theoretic Evaluation of Values Clarification on Parental Beliefs and Intentions Toward Genomic Sequencing for Newborns - Paquin, Ryan S. (Soc Sci Med, 2018)
Decision aids commonly include values clarification exercises to help people consider which aspects of a choice matter most to them, and to help them make decisions that are congruent with their personal values and preferences. Using a randomized online experiment, we examined the influence of values clarification on parental beliefs and intentions about having genomic sequencing for newborns. We recruited 1,186 women and men ages 18–44 who were pregnant or whose partner was pregnant or planning to become pregnant in the next two years. Participants (N = 1,000) completed one of two versions of an online decision aid developed as part of a larger project examining the technical, clinical, and social aspects of using exome sequencing to screen newborns for rare genetic conditions. The education-only version provided information about using genomic sequencing to screen newborns for medically treatable conditions. The education-plus-values-clarification version included the same information, along with a values clarification exercise in which participants classified as important or unimportant five reasons in support of having and five reasons against having their newborn undergo genomic sequencing. We conducted partial correlations, regression analysis, and MANCOVAs with sex, health literacy, and experience with genetic testing as covariates. Participants who completed the decision aid with the values clarification exercise agreed less strongly with four of the five statements against sequencing compared to participants who viewed the education-only decision aid. The groups did not differ on agreement with reasons in support of sequencing. Agreement with four of five reasons against genomic sequencing was negatively associated with intentions to have their newborn sequenced, whereas agreement with all five reasons in support of sequencing were positively associated with intentions.